An analysis of sustainability and channel coordination in a three-echelon supply chain. Issue 1 (11th January 2021) - Huang, Ruting; Yao, Xin
Abstract : Purpose: The purpose of this paper is to investigate the decision behaviors and channel coordination of a sustainable three-echelon supply chain with retailer-led game setting. Design/methodology/approach: The authors develop game-theoretic models to examine the decision behaviors of channel members in a three-echelon supply chain consisting of one supplier, one distributor and one dominated retailer. The authors first formulate two models for centralized decision and decentralized decision. And then this paper proposes sub-supply chain coordination and a two-tariff contract to coordinate the full supply chain. Finally, some management insights are obtained with a case study. Findings: The authors find that when faced with environmentally conscious consumers, the channel members can benefit from higher greening level; however, higher cost of green technologies would have negative impacts on manufacturer's effort. The analysis also shows that cooperation among players can improve the supply chain performance and help with environmental improvement. Research limitations/implications: The findings provide important managerial insights for the three-echelon supply chain to achieve sustainable goals where the retailer bears the environmental responsibility. However, this paper also has some limitations with assuming risk-neutral channel members and symmetric information. Originality/value: The findings of the study contribute to coordination and collaboration in sustainability of supply chains. The results provide important managerial insights for the three-echelon supply chain to achieve sustainable goals.